Temporal Finitude, Embodied Perception and Ethical Call: Synthesising Perspectives of Heidegger, Merleau-Ponty, and Levinas on Encountering “the Other” - Lasker, Michael (The Stellenbosch Socratic Journal, 2025)
Phenomenology has consistently concerned itself with the encounter with "the Other" and the implications of this encounter for the self, yet some of the principal expounders of Phenomenology differ significantly in their views. For Martin Heidegger (1962), it serves as a catalyst for the confrontation with the finitude of the self, as defined by one's own temporal and spatial limitations enforced by one's mortality. Maurice Merleau-Ponty (2012) moves from this abstract ontological engagement towards a theory centred on the physicality of the perception of and interaction between physical bodies. Emmanuel Levinas (1969) further shifts towards an ethical perspective, which views the encounter with "the Other" not as a catalyst towards authenticity or as a co-creator of meaning, but as a fulcrum by which the self is leveraged beyond its limitations in order to respond to the ethical responsibility it has towards the vulnerability of "the Other". Despite their differences, each of these philosophers offer a valuable contribution towards the understanding of what it means to encounter another being, yet there is want for a synthesis of these contributions. This article aims to compare these differing perspectives to demonstrate the multifaceted nature of the encounter with "the Other", and thus highlight the necessity of understanding each philosopher's perspective in conjunction, rather than in conflict, with each other. This article concludes that a comprehensive attempt at a synthesis is both possible and worth revisiting.